Application of the Andragogi Approach in the Development of Al-Qur’an Learning at the Mahad Umar bin Al-Khattab Sidoarjo Student Islamic Boarding School: Penerapan Pendekatan Andragogi dalam Pembinaan Pembelajaran Al-Qur’an di Pesantren Mahasiswi Mahad Umar bin Al-Khattab Sidoarjo - Nisa, Zahrotun; Romadlon, Dzulfikar Akbar (Indonesian Journal of Innovation Studies, 2026)
General Background: Qur’anic learning in student pesantren requires an approach aligned with adult learners’ characteristics, emphasizing independence, experience, and active participation. Specific Background: Mahad Umar bin Al-Khattab Sidoarjo applies andragogy in Qur’anic learning for female university students residing in its boarding program. Knowledge Gap: Previous studies have mainly addressed adult Qur’anic learning and reading outcomes, while this study examines its implementation in students’ academic and community contexts. Aims: This study describes planning, implementation, monitoring, and evaluation of andragogical Qur’anic learning. Results: Needs identification, structured murojaah, partnership, daily mutabaah, routine evaluation, mentoring, and flexible arrangements support memorisation, discipline, motivation, academic learning, and Qur’anic teaching competence. Novelty: The study combines partnership, daily monitoring, motivation, and appreciation within a student boarding context. Implications: The model provides a reference for other student pesantren developing Qur’anic learning for adult learners. Key Findings Highlights Structured murojaah supports sustained Qur’anic memorisation. Partnership develops active participation and teaching competence. Daily mutabaah and appreciation reinforce learner responsibility. Keywords: Andragogical Learning, Qur’anic Learning, Student Pesantren, Qur’anic Memorisation, Partnership Learning